The Impact of Sustainable Marketing on Improving Business Reputation Applied to Egyptian Companies - Anwar, Sahar Mohamed (The Arab Journal of Administration, 2025)
In light of the environmental and social changes that the world is witnessing, clients or consumers have become more aware of the importance of sustainability. This has led to a shift in their purchasing behavior, as they become more inclined to purchase products from companies that adhere to sustainable practices. Sustainable marketing refers to a set of marketing strategies and practices that aim to achieve sustainable economic and business objectives while taking into account environmental and social aspects. This includes marketing sustainable products, as well as marketing sustainability values. Research shows that sustainable marketing has a positive impact on improving business reputation. Companies that adhere to sustainable practices are seen as more responsible and ethical. This can lead to increased confidence in the brand and improved relationships with clients or customers... The current study aimed to measure the impact of sustainable marketing on improving business reputation. The descriptive analytical method was used in this study, where data was collected through a questionnaire that was distributed to a non-random sample, its size was 96 of public ( clients or consumers ) in Cairo and Giza Governorates. The results of the study showed that sustainable marketing has a positive impact on improving business reputation. The research presented a set of recommendations, the most important of which is the need for commercial companies to practice sustainable marketing, as a basic strategy for improving commercial reputation. It is necessary for commercial companies to communicate effectively with consumers about their sustainable practices, in order to increase their awareness of these practices. It is also necessary for commercial companies to focus on measuring the impact of their sustainable practices on business reputation, in order to constantly improve these practices.